KEADILAN DALAM HUBUNGAN HUKUM ANTARA DOSEN PERGURUAN TINGGI SWASTA DENGAN BADAN PENYELENGGARA PERGURUAN TINGGI - Miftakhul Huda (Yuridika, 2017)
The position of the lecturer as a professional educator who runs the college tridharma causes the legal relationship of the lecturer of Private Higher Education with the Private University Administration Board to have its own distinct characteristic from the legal relationship in the labor law which is characterized by a limited relationship or sub-ordinate (dienstverhovding) Which characterizes the relationship between the government/the authorities and the people. The construction of these different legal relationships causes the courts in Indonesia to have no strong foothold regarding the absolute authority to adjudicate disputes or disputes arising in the legal relations of Private University lecturers with the Private University Organizing Body. Thus, it is necessary to create a new concept of legal relationship in parallel position whose basic rights and obligations are determined by the Law because the implementation of education should be the obligation of the government so that the people who assist its implementation should be given optimal protection both in terms of freedom of academic pulpit and welfare protection of lecturers